PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA DAN MOTIVASI KARYAWAN PADA CV MEDIA KREASI BANGSA - Adhitomo Wirawan; Ismi Nur Afani (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This study aims to determine the effect of both simultaneously and partially between reward and punishment on employees performance and motivation at CV. Media Kreasi Bangsa. This study used Multiple Linear Regression method, while the sample in this study using probability sampling technique where the sample was taken using proportionate stratified random which amounted to 132 employees. The research instrument used interview, questionnaire, observation, and documentation. The result of this study is the reward variable has a positive effect on the performance of this matter seen from t arithmetic (2,363) bigger than t table (1,65) with significant level (0,020 <0,05). Reward variable has a positive effect on this motivation seen from t arithmetic (4,289) bigger than t table (1.65) with significant level (0,000 <0,05). There is a simultaneous influence between reward and punishment variable on the performance of this matter seen from F arithmetic (21,162) bigger than F table (3,07) with significant level (0,000 <0,05). The punishment variable has a positive effect on the performance of this matter seen from t arithmetic (5,309) bigger than t table (1.65) with significant level (0,000 <0,05). The punishment variable has a positive effect on this motivation seen from t arithmetic (3,587) bigger than t table (1.65) with significant level (0,000 <0,05). There is simultaneous influence between reward and punishment variables on this motivation seen from F count (20,557) bigger than F table (3,07) with significant level (0,000 <0,05).